Atenção à saúde de crianças e adolescentes vivendo com HIV/AIDS: avaliação dos familiares/cuidadores - Silva, Clarissa Bohrer da (2014)
The objective was to assess the presence and extent of the attributes of primary health care to children and adolescents living with HIV/AIDS, according to the PCATool-Brazil Child version instrument. This dissertation is part of a matrix design, which is a cross-sectional survey, conducted in an outpatient facility for pediatric infectious diseases, with family members/caregivers of children and adolescents living with HIV/AIDS. Data collection was carried out by applying the PCATool-Brazil Child version instrument. The analysis was performed with the software SAS version 9.3. Respected to the ethical aspects in accordance with Resolution 196/96, in force during the study period. The population amounted to 71 family/caregivers, 51% of which children/adolescents were between 13 and 19 years old, 51% lived in other cities, 54% the mother was the primary caregiver and 54% had income below 1000 actual. The clinical profile, 90% of children/adolescents acquired HIV through vertical transmission, 51% was receiving treatment. As regards the use of health services, 94% knew the nearest health service, 95% had a Primary Health Care service (PHC), however, only 44% took the child/adolescent in this service. To evaluate the quality of health care for children and adolescents living with HIV/AIDS were identified as regular source of care PHC service and, mostly, specialized service to HIV (78.8%). The results showed no statistically significant differences between services, as both had satisfactory scores values (mean ≥6,6) for attributes of: First Contact Access - use; First Contact Access - accessibility; Longitudinality; Coordination - integration of care; Coordination - information system; Integrality - available services. On the analysis of attributes, no service (specialized and PHC) showed satisfactory value overall score, but had near ideal (average 6.43 and 6.13, respectively). Furthermore, no sociodemographic variable, clinical and service usage was associated with high overall score. There was no distinction between health services, however emphasize the need to integrate both services aiming to improve care and improvement of its attributes, which implies reformulations in the aspects of structure and performance. The study had a limitation by the size of the population and it was produced in a medium-sized city, and the generalization of data should be made with caution.